2023
DOI: 10.3390/jtaer18010027
|View full text |Cite
|
Sign up to set email alerts
|

‘Stimuli Are All Around’—The Influence of Offline and Online Servicescapes in Customer Satisfaction and Repurchase Intention

Abstract: In the last decade, multichannel retailing has grown at a significant rate, especially in emerging markets such as Indonesia, where retailers have embraced multichannel marketing to heighten the customer shopping experience. Improved servicescape—the environment where services are provided and where interaction with customers occurs—may help enhance the customer experience. While the role of servicescapes has been analyzed in online or offline contexts previously, this research adopts a multichannel view and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 64 publications
1
9
0
3
Order By: Relevance
“…This is also supported by research conducted by (Ananda, Hanny, Hernández-García, & Prasetya, 2023) that consumer satisfaction (customer satisfaction) is positively related and affects consumer repurchase (repurchase intention) in multichannel retail. The relationship between the influence of customer satisfaction on customer retention is quite high at 67.3%, which means that increasing customer satisfaction can affect customer retention at Alfagift.…”
Section: The Effect Of E-service Quality On Word Of Mouthsupporting
confidence: 58%
“…This is also supported by research conducted by (Ananda, Hanny, Hernández-García, & Prasetya, 2023) that consumer satisfaction (customer satisfaction) is positively related and affects consumer repurchase (repurchase intention) in multichannel retail. The relationship between the influence of customer satisfaction on customer retention is quite high at 67.3%, which means that increasing customer satisfaction can affect customer retention at Alfagift.…”
Section: The Effect Of E-service Quality On Word Of Mouthsupporting
confidence: 58%
“…It has been argued that consumers think that webrooming saves time, effort, and energy and causes more appropriate purchase decisions compared with brick-and-mortar showrooms. Studies have suggested that offline stores still hold prime importance in omnichannel strategies and that the interplay between the benefits of the offline channel and value-added services of online channels enable retailers to provide a unified customer experience [31,38]. Moreover, webrooming behavior creates increased control and responsibility in consumers compared with showrooming behavior [1].…”
Section: Hypotheses Of Study 221 Webrooming Behaviorsmentioning
confidence: 99%
“…This study provides insights from multiple cases into four servicescapes, which are utilized to illustrate the physical and social environments in which individuals live [15]. Servicescape is a model developed by Booms and Bitner to emphasize the impact of the physical environment in which a service process takes place [16]. We illustrate how value is co-created in many-to-many networks connected through mobile payments.…”
Section: Introductionmentioning
confidence: 99%